A UPLC–MS/MS method for analysis of vancomycin in human cerebrospinal fluid and comparison with the chemiluminescence immunoassay. (20th February 2017) - Mei, Shenghui; Wang, Jiaqing; Zhu, Leting; Chen, Ruiling; Li, Xingang; Chen, Kai; Chen, Guangqiang; Zhou, Jianxin; Wang, Qiang; Zhao, Zhigang
Abstract: Vancomycin (VCM) is clinically used in treating patients with postoperative intracranial infections. The cerebrospinal fluid (CSF) concentration of VCM varies greatly among patients. To guide the dosage regimens, monitoring of VCM in CSF is needed. However a method for analysis of VCM in human CSF is lacking. An ultraperformance liquid chromatography tandem mass spectrometry (UPLC–MS/MS) was developed and validated for analysis of VCM in human CSF, and the agreement of UPLC–MS/MS and chemiluminescence immunoassay (CLIA) in the analysis of CSF VCM was evaluated. The ion transitions were m/z 725.5 > 144.1 for VCM and m/z 455.2 > 308.2 for methotrexate (internal standard). The agreement between UPLC–MS/MS and CLIA was evaluated by Bland–Altman plot in 179 samples. The calibration range of the UPLC–MS/MS method was 1–400 mg/L. The inaccuracy and imprecision were −0.69–10.80% and <4.95%. The internal standard normalized recovery and matrix factor were 86.14–99.31 and 85.84–92.07%, respectively. The measurements of CLIA and UPLC–MS/MS were strongly correlated ( r > 0.98). The 95% limit of agreement of the ratio of CLIA to UPLC‐MS/MS was 61.66–107.40%. Further studies are warranted to confirm the results.